Quantitative analysis of cells of the pancreatic islets in rats under effect of alloxan - Lima, Marcus Aurelho; Lima, Lilian Margareth Biagioni; Rita, Danielle Patrícia Castanheira; Navarro, Fábio Castilho; Tatsukawa, Ranaia Santana; Pereira, Gilberto Araújo; Reis, Luiz Carlos; Abreu, Marta Elena Araújo; Borges, Maria de Fátima (Medicina (Ribeirao Preto), 2001)
In the present study, we verified the influence of alloxan over the cells of pancreatic islet of rats, performing quantitative analysis of Twenty male rats (Rattus norvegiccus) were used of Wistar line, disposed in 2 groups of 10 rats on each, being a control group and an experimental one. After fasting of 36 hours, 40 ml/Kg of monohydrated of alloxan was administrated by intravenous via and about 30 minutes after, the animal was offered food. At the end of 10 days of observation, animals were sacrificed. Samples of different regions of pancreas were selected and undergone to a histological process and stained with hematoxilin-eosin. To the immunohistochemical study, anti-insulin, anti-glucagon and anti-somatostatin antibodies were used. Quantitative analysis was performed in eight most representative pancreatic islets of each animal. Results were considered significative when p<0.05. There was a significative reduction in the number of a, b and d cells through immunohistochemical study.b cells and a significative increase in the number of d cells. Results reinforce the assertion that alloxan exerts significative influence over the pancreatic b cells, destructing the islets and over the pancreatic d -cells, which has already been observed in other studies. However, the action mechanism of alloxan over the pancreatic b -and d -cells was not completely shown, therefore having necessity of more studies to its elucidation.